Zero Fail : The Rise and Fall of the Secret Service - Leonnig, Carol (New York : Random House, 2021)
"Carol Leonnig has been covering the Secret Service for The Washington Post for most of the last decade, bringing to light the gaffes and scandals that plague the agency today--from a toxic work culture to outdated equipment and training to the deep resentment among the ranks with the agency's leadership. But the Secret Service wasn't always so troubled. The Secret Service was born in 1865, in the wake of the assassination of Abraham Lincoln, but its story begins in earnest in 1963, with the death of John F. Kennedy. Shocked into reform by their failure to protect the president on that fateful day, this once-sleepy agency was rapidly transformed into a proud, elite unit that would finally redeem themselves in 1981 by valiantly thwarting an assassination attempt against Ronald Reagan. But this reputation for courage and efficiency would not last forever. By Barack Obama's presidency, the Secret Service was becoming notorious for break-ins at the White House, an armed gunman firing at the building while agents stood by, a massive prostitution scandal in Cartagena, and many other dangerous lapses. To expose the these shortcomings, Leonnig interviewed countless current and former agents who risked their careers to speak out about an agency that's broken and in desperate need of a reform"--.
Protecting Lancer -- Tempting the devil -- Three shots in Dallas -- No time to grieve -- One last day on the trail -- The president's spies -- A casual walk to church -- Battening down the hatches -- Night of the long knives -- A happy service, a rising threat -- A rock star president -- The intern -- Scrambling on 9/11 -- "You don't belong here" -- "He predicted all of it" -- "Obama will die. KKK forever! " Or "He'll be shot sure as hell." -- Sullivan's crew -- The night bullets hit the white house -- "I woke up to a nightmare" -- Sullivan's struggles -- Outed -- A new sheriff in town or the first female director -- A listing ship -- "He's in the house" -- Clancy's turn -- Chaos candidate -- Taking a hit for Trump.
Includes index.
Keywords: United States. -- Secret Service -- History; United States. -- Secret Service -- Administration; Secret service -- History -- United States; Presidents -- Protection -- United States -- History; Presidents -- Assassination -- United States -- History; Presidents -- Assassination attempts -- History